The Cowboy - Wexler, Abe; Bradbury, Robert North; Stout, Archie; Steele, Bob; Sedgwick, Josie; Laroux, Carmen (The National Center for Jewish Film, 2006)
Yes, it's just your typical all-Yiddish shoot-'em-up: a small boy falls out of a covered wagon on its way West and shows up years later as a quick trigger cowboy. When he is unjustly accused of theft, a gunfight breaks out to the strains of "Oyfn Pripitchik." This spoof was made by adding a Yiddish dialogue to the "Son of Oklahoma", a 1932 Hollywood Western. A hilarious short for a Yiddish-speaking audience! [jewishfilm.org]
Keywords: DVD-Video